The Effectiveness of Postmodern Approach Group Counseling: SFBC and Narrative Therapy in Improving Academic Resilience of Bullying Survivors - Aditya Oktava, Muhammad; Mulawarman, Mulawarman; Awalya, Awalya (Universitas Negeri Semarang, 2022)
Resilience is an important sub-factor necessary for students to improve their learning achievement. Up to now, students as bullying survivors experience decrease in their academic resilience. Thus, the present study attempted to determine the effectiveness of group counseling with SFBC and Narrative Therapy approaches to improve the academic resilience of the students in SMK Negeri Batealit in Jepara Regency. It used an experimental method with a randomized pretest-posttest comparison group design and purposive sampling to obtain 16 students as subjects of the study with low academic resilience. The student’s data were collected using Academic Resilience Scale (ARS) designed independently by the researchers with the validity coefficient of (0.249-0.780) and an alpha reliability of 0.884. Findings indicated that the intervention of group counseling with SFBC and Narrative Therapy approaches has been effective to improve the academic resilience of bullying survivors in SMK Negeri 1 Batealit in Jepara Regency. The interesting thing from the results of this study is that self-efficacy is the most influential aspect in shaping students' academic resilience.